2009
DOI: 10.1007/s12272-009-2008-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromone glycosides and hepatoprotective constituents of Hypericum erectum

Abstract: Two chromone glycosides, hyperimone A [7-(beta-D-glucopyranosyloxy)-5-hydroxy-2-(1-methylethyl)-4H-1-benzopyran-4-one (1)] and hyperimone B [7-(beta-D-glucopyranosyloxy)-5-hydroxy-3-methyl-4H-1-benzopyran-4-one (2)], together with six known compounds were isolated from the methanolic extract of the whole plant of Hypericum erectum. 1,3,5,6-Tetrahydroxyxanthone (5) and I3, II8-biapigenin (6) showed moderate hepatoprotective activity with EC(50) values of 160.2 +/- 0.6 microM and 217.7 +/- 1.3 microM, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Furthermore, An et al [57] also showed that 1,3,5,6-tetrahydroxyxanthone and I3, II8-biapigenin, isolated from the methanolic extract of the whole plant of H. erectum , had moderate hepatoprotective activity against tacrine-induced cytotoxicity in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, An et al [57] also showed that 1,3,5,6-tetrahydroxyxanthone and I3, II8-biapigenin, isolated from the methanolic extract of the whole plant of H. erectum , had moderate hepatoprotective activity against tacrine-induced cytotoxicity in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperricum erectum, Sarcandra glabra etc. with hepatoprotective glycosides are also reported in the literature (An et al, 2009;Li et al, 2006).…”
Section: Discussionmentioning
confidence: 78%
“…Scindapsus officinalis stems [31] Ammi visnaga fruits [32] Knoxia corymbosa [33] Pancratium biflorum roots [34] Panacratium biflorum flowering bulbs [35] Pancratium maritimum L. fresh bulbs [36] Peucedanum austriacum [37] Tecomella undulata bark [38] Adina rubescens leaves [39] Dryopteris fragrans [40] Staphylea bumalda leaves [20] Immunomodulatory activity inhibited the proliferation of murine B lymphocytes in vitro at 10 Hypericum henryi aerial parts [41] Hypericum erectum [42] No reported biological activity Hyperimone A Urachromone B Hypericum henryi aerial parts [41] No reported biological activity…”
Section: -O-(6 -Galloyl)-β-dglucopyranosyl-5hydroxychromonementioning
confidence: 99%